Unravelling lifecycles & physics of radio-loud AGN in the SKA era - Kapinska, A.; Hardcastle, M.; Jackson, Carole; An, T.; Baan, W.; Jarvis, M. (Proceedings of Science, 2014)
Radio-loud AGN (> 10 22 W Hz-1 at 1.4 GHz) will be the dominant bright source population detected with the SKA. The high resolution that the SKA will provide even in wide-area surveys will mean that, for the first time sensitive, multi-frequency total intensity and polarisation imaging of large samples of radio-loud active galactic nuclei (AGN) will become available. The unprecedented sensitivity of the SKA coupled with its wide field of view capabilities will allow identification of objects of the same morphological type (i.e. the entire FR I, low- and high-luminosity FR II, disturbed morphology as well as weak radio-emitting AGN populations) up to high redshifts (z ~ 4 and beyond), and at the same stage of their lives, from the youngest CSS/GPS sources to giant and fading (dying) sources, through to those with restarted activity radio galaxies and quasars. Critically, the wide frequency coverage of the SKA will permit analysis of same-epoch rest-frame radio properties, and the sensitivity and resolution will allow full cross-identification with multi-waveband data, further revealing insights into the physical processes driving the evolution of these radio sources. In this chapter of the SKA Science Book we give a summary of the main science drivers in the studies of lifecycles and detailed physics of radio-loud AGN, which include radio and kinetic luminosity functions, AGN feedback, radio-AGN triggering, radio-loud AGN unification and cosmological studies. We discuss the best parameters for the proposed SKA continuum surveys, both all-sky and deep field, in the light of these studies.